Placental Maspin Gene Expression Pattern May Be Used to Distinguish Between Preeclampsia and Intrauterine Growth Restriction - Gogsen Onalan; Yunus Kasim Terzi; Yusuf Aytac Tohma; Erkan Yurtcu; Esra Kuscu; Feride Iffet Sahin; Hulusi Bulent Zeyneloglu (Gynecology Obstetrics & Reproductive Medicine)
Objective: Maspin is one of the members of serin protease inhibitor superfamily, and acts as a tumor suppressor protein. Here we report maspin expression in placental tissues of preeclampsia or intrauterine growth retardation pregnancies.